2017
DOI: 10.1186/s13722-017-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of the HIV care continuum in Southern New England for people with drug or alcohol use and living with HIV/AIDS: perspectives of HIV surveillance experts and service providers

Abstract: Background Contemporary studies about HIV care continuum (HCC) outcomes within substance using populations primarily focus on individual risk factors rather than provider- or systems-level influences. Over 25% of people living with HIV (PLWH) have substance use disorders that can alter their path through the HCC. As part of a study of HCC outcomes in nine small cities in Southern New England (population 100,000–200,000 and relatively high HIV prevalence particularly among substance users), this qualitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Salient to this is the undercurrent of mental health problems and substance use, which can hinder optimization of provider approaches to engage patients into the care continuum. This finding aligns with other studies documenting the significance of substance use and mental health states in engagement in the HCC, [22][23][24]26,27 and highlights the need for providers to be aware of the context of patients' lives and appreciate potential threats to overall patient well-being and engagement. Another threat to optimal well-being is the patient's health literacy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Salient to this is the undercurrent of mental health problems and substance use, which can hinder optimization of provider approaches to engage patients into the care continuum. This finding aligns with other studies documenting the significance of substance use and mental health states in engagement in the HCC, [22][23][24]26,27 and highlights the need for providers to be aware of the context of patients' lives and appreciate potential threats to overall patient well-being and engagement. Another threat to optimal well-being is the patient's health literacy.…”
Section: Discussionsupporting
confidence: 88%
“…To address the gap in the literature, the aim of this study was to describe provider approaches to engage patients into the HCC. Although the findings from this study support previous understandings about patient-provider interactions in health promotion, [22][23][24][25] contextualizing providers' experiences reveals the intricacies of specific approaches to address patient vulnerabilities. The provider narratives revealed that efforts and approaches aligned across disciplines indicating the influence of evidence-based practice in HIV prevention and treatment.…”
Section: Discussionsupporting
confidence: 58%
“…Policy-level factors associated with health literacy include factors such as funding for and mandating of health interpreters and health advocates, policies regarding the use of plain language communications, and so forth. The SEM has been used to understand a wide variety of health factors, beliefs, and behaviors, from confidence in the human papillomavirus (HPV) vaccine [ 28 ], to access to human immunodeficiency virus (HIV) treatment [ 29 ], to students’ food choices while at school [ 30 ], to getting the flu shot [ 31 ], to being physically active [ 32 , 33 ], and to sedentary behavior [ 34 ]. The current qualitative study focused on exploring interpersonal and organizational levels of SEM that may impact patients at FQCHCs in Rhode Island.…”
Section: Methodsmentioning
confidence: 99%
“…Systems issues must also be addressed to close HIV care continuum gaps for people who use drugs. Qualitative interviews with public health and HIV service providers in Connecticut identified the need to increase mental health and substance use services and peer navigation/case management services and the need to decrease service agency stigma as key barriers and potential facilitators for improving HIV testing, engagement, and treatment [ 10 ]. Idrisov et al [ 11 ] reported no association between individual injection use histories and HIV outcomes, suggesting that systems issues may also prove a dominating contributor to HIV outcomes in Russia, obscuring individual factors.…”
mentioning
confidence: 99%